A Comprehensive Analysis of Mobile Ad-Hoc Routing Protocols Under Varying Node Densities - Kaler, Manpreet Kaur; Malhotra, Sonia (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Mobile ad-hoc network (MANET) is a well known wireless technology being used in present wireless systems and it influences the development of new structures and theories for the communication. The mobile communication in wireless field consists of various nodes communicating with each other through the relay nodes using multi-hope network system or directly. The MANET consists of many routing protocols. Dynamic communication field is mainly dealing area for these routing protocols of MANET. Now-a-days as mobile applications are increasing frequently, It is primary need to analyze these routing protocols to work with high node density and more data load. It motivates the use of various performance comparisons of AODV, DSR and OLSR protocols in mobile ad-hoc network. The comparison represents justified, more effective and reliable protocol for required mobile application. We can analyze these protocols performance on the basis of various matrices like End to End delay, Network load, Re-Transmission attempts and Throughput Using OPNET simulator software tool. The graphical representations are presented here to support the results carried out in this paper.